Identification of proteins, drying oils, waxes and resins in the works of art micro‐samples by chromatographic and mass spectrometric techniques. Issue 3 (14th December 2017) - Witkowski, Bartłomiej; Duchnowicz, Anna; Ganeczko, Monika; Laudy, Agnieszka; Gierczak, Tomasz; Biesaga, Magdalena
Abstract: Simplified method for simultaneous identification of proteins, drying oils, waxes, and resins in the works‐of‐art samples was developed. Liquid chromatography with mass spectrometry and gas chromatography with mass spectrometry were used to identify natural materials most frequently encountered in historical paintings. Protein binders were extracted with ammonia and purified using miniaturized solid‐phase microextraction (Omix tips) to efficiently suppress matrix interferences. Zwitterionic stationary phase was used for separation of 16 underivatized amino acids analysis with hydrophilic interaction liquid chromatography that was subsequently quantified with liquid chromatography with mass spectrometry. Gas chromatography with mass spectrometry was used to analyze drying oils, waxes, and resins after one‐step saponification/transmethylation with ( m ‐trifluoromethylphenyl)trimethylammonium hydroxide (Meth‐Prep II). While the drawback of this reagent is low reactivity towards hydroxyl groups, sample pretreatment was much simpler as compared to the other methods. Fatty acids derivatization with the Meth‐Prep II reagent was compared with their silylation using N, O ‐bis(trimethylsilyl) trifluoroacetamide/trimethylchlorosilane mixture. It was concluded that fatty acids analysis as their methyl esters instead of trimethylsilyl esters had a minor impact on the method sensitivity. The developed method was used to analyze samples from 16 th and 17 th century historical paintings.